Síntese de β-feniltiossemicarbazonas derivadas de isatina e estudo in vitro da atividade antibacteriana - Silva, Everton da Paz (2020)
The indole nucleus, contained in isatin, is present in several bioactive molecules and this makes isatin an excellent synthetic block for the development of new potentially active compounds. Isatin derivatives are commonly reported in the literature with different biological activities and thiosemicarbazones stand out for their synthetic simplicity and high biological potential. Thus, this work aimed of analogous series synthesis of β-phenyl thiosemicarbazones derived from isatin by irradiation of microwave and investigation of antibacterial activity. Among these compounds, eight are unpublished. Preliminary experiments were carried out by varying the parameters of catalysis, temperature and reaction time in order to define a general method of synthesis to obtain the compounds. Isatin derivatives were prepared and used as intermediates in the synthesis of thiosemicarbazones. The series of β-thiophenylsemicarbazones was obtained in reactions assisted by microwave radiation, lasting 10 min in the presence of acetic acid as a catalyst. The yields obtained varied from 50-94% and were compared with those presented in the literature. All compounds were characterized by 13C and 1H NMR spectroscopy. The method developed for the synthesis of these compounds in microwave reactor proved to be a useful and efficient to obtain the products in a short reaction time. The in silico study was carried out and indicated that the compounds are in compliance with the rule of Lipinski and ADME, presenting a satisfactory oral bioavailability. The compounds were evaluated for antibacterial activity in the strains of S. aureus, E. coli and P. aeruginosa and thiosemicarbazone derived from 5-chloro-1-methyl-isatin (64) was the only one capable of inhibiting the growth of microorganisms with MIC of 562.5 μg / mL, indicating strong inhibitory activity.